Optimized Ultrasonic-Assisted Extraction of Polysaccharides from Chinese Traditional Medicinal Plant Paris fargesii Using Orthogonal Design - Gang Xiang, Dan Wang, Gui-Hua Zou, Xing Huang, Meng-Liang Tian and Feng Gao (Journal of Applied Pharmaceutical Science, 2013)
Paris fargesii is a famous Chinese traditional medicinal plant used as antipyretic, antidotal, antiphlogistic and analgesic. This research aimed at the determination of the total polysaccharides contents in P. fargesii, which were collected from Baoxing country of Sichuan Province in order to get the optimized extraction technology. Ultrasonic method was adopted in the extraction of total polysaccharides from P. fargesii. Through single factor experiment and orthogonal test, the effects of ultrasonic extraction conditions on the total polysaccharides extraction were measured, including solid-liquid ratio, ultrasonic temperature, ultrasonic power and ultrasonic time. Then colorimetric method was applied for the assaying. The optimized extraction conditions of total polysaccharides from P. fargesii were as follows: ultrasonic power: 600w, solid-liquid ratio: 1:20, ultrasonic extraction time: 1.5h and ultrasonic temperature: 90â„ƒ. Under the optimum parameters, the total polysaccharides extraction efficiency was 0.0715%.
Keywords: Paris fargesii, total polysacchar